2023
DOI: 10.1126/science.adf9325
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes after pregnancy-induced displacement of preexisting microchimeric cells

Tzu-Yu Shao,
Jeremy M. Kinder,
Gavin Harper
et al.

Abstract: Pregnancy confers partner-specific protection against complications in future pregnancy that parallel persistence of fetal microchimeric cells (FMcs) in mothers after parturition. We show that preexisting FMcs become displaced by new FMcs during pregnancy and that FMc tonic stimulation is essential for expansion of protective fetal-specific forkhead box P3 (FOXP3)–positive regulatory T cells (T reg cells). Maternal microchimeric cells and accumulation of T reg ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“… 77 Important next-steps include investigating how KLF2 controls IL-10 expression, and KLF2+ cells in other physiological contexts that require IL-10 (e.g., reproductive tolerance, antimicrobial host defense). 78 80 A related priority involves evaluating lineage commitment stability of commensal primed KLF2+ CD4 cells, potential history of prior FOXP3 expression by suppressive FOXP3-negative KLF2+ cells, 81 and whether KLF2+ cells can differentiate into pro-inflammatory effector lineages, and the commensal priming conditions that stimulate KLF2 and IL-10 co-expression in antigen-experienced CD4 cells. Nonetheless, an instructive alternative framework for investigating intestinal inflammation from a non-FOXP3+ Treg-centric perspective is unveiled through identification of KLF2 as a distinct suppressive CD4 subset required for averting commensal microbiota-induced inflammation in mice, and blunted accumulation of these cells in human Crohn’s disease.…”
Section: Discussionmentioning
confidence: 99%
“… 77 Important next-steps include investigating how KLF2 controls IL-10 expression, and KLF2+ cells in other physiological contexts that require IL-10 (e.g., reproductive tolerance, antimicrobial host defense). 78 80 A related priority involves evaluating lineage commitment stability of commensal primed KLF2+ CD4 cells, potential history of prior FOXP3 expression by suppressive FOXP3-negative KLF2+ cells, 81 and whether KLF2+ cells can differentiate into pro-inflammatory effector lineages, and the commensal priming conditions that stimulate KLF2 and IL-10 co-expression in antigen-experienced CD4 cells. Nonetheless, an instructive alternative framework for investigating intestinal inflammation from a non-FOXP3+ Treg-centric perspective is unveiled through identification of KLF2 as a distinct suppressive CD4 subset required for averting commensal microbiota-induced inflammation in mice, and blunted accumulation of these cells in human Crohn’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Recently, reporter murine models have been used to study both fetal and maternal microchimerism, with the fluorescent reporter detected via immunofluorescence microscopy or quantified via PCR, flow cytometry and other high-dimensional phenotyping techniques such as mass cytometry by time-of-flight (CyTOF). [15,24,29,30] Flow cytometry has also been used to detect circulating fetal EVs by detecting presence of fetal or placental proteins such as HLA-G or placental alkaline phosphatase (PLAP). [31]…”
Section: Significance Of Fetal Microchimerism and Circulating Fetal E...mentioning
confidence: 99%
“…[22] A comprehensive review of fetal microchimerism that utilized an evolutionary framework to explain this phenomenon has been previously discussed by Boddy et al [23] Recent murine studies on fetal microchimerism have shown that only a set of microchimeric cells can exist in an individual at a time, which means that maternal microchimeric cells can be displaced from a primigravid individual by cells from her ongoing pregnancy, and these eventual fetal microchimeric cells get displaced by new fetal cells from a succeeding pregnancy. [24] This was contrasted with the idea of an individual being comprised of an expanded collection of microchimeric cells acquired from cross-generation transfer, that is, a "microchiome". [7] In addition to fetal microchimeric cells, cellular components, specifically extracellular vesicles (EVs, e.g., exosomes, microvesicles, and apoptotic bodies) can leave the fetus, [25] migrate to the maternal circulation [26] and traffic to the heart and other tissues raising the exciting possibility that they bring the necessary biomolecules including proteins and small RNAs which could regulate function at the level of cells, tissues, and organs.…”
Section: Significance Of Fetal Microchimerism and Circulating Fetal E...mentioning
confidence: 99%
“…For example, the pool of FMc increases with each subsequent pregnancy in the maternal body, hereby expanding the diversity of FMc in the mother. In consequence, younger siblings are considered to receive a more diverse composition of MMc, which not only includes maternal cells, but can also contain cells from older siblings, or their grandmother and possibly even elder siblings of their mother (uncles, aunts) (Kinder et al, 2017 ; Shao et al, 2023 ). This pool of trans- and intergenerational microchimeric cells within an organism has been termed microchiome.…”
Section: Introductionmentioning
confidence: 99%
“…This “advanced” immune tolerance is mediated by the expansion of NIMA-specific T reg cells in the female fetus in mice, accompanied by the long-term plasticity of FoxP3 expression. Interestingly, in mice MMc-associated expansion of NIMA-specific T reg cells are being eliminated once these female offspring become pregnant themselves, suggesting a reprogramming of pregnancy-imprinted immunological memory (Thiele et al, 2019 ; Shao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%